Drug Control during the Covid -19 Pandemic in the Faucalt Governmentality Perspective (Study of PT. Rifanti Asti City Sorong) - Rosnani, Rosnani; Saeni, Agil; Rumakat, Lailatul Qadriani; Kalagison, Miryam Diana (Universitas Negeri Makassar, 2023)
This research aims to study, analyze and interpret: Drug Control during the Covid-19 Pandemic from a Faucalt Governmentality Perspective (PT. Rifanti Asti Study, Sorong City). Because if you look at the phenomenon, there are still many complaints from the public regarding government regulations and policies during the Covid-19 pandemic. 19, as this research is descriptive analysis using a qualitative approach, data was obtained from a number of informants. The research results show that, drug control implemented by PT. Rifanti Asti during the Covid-19 pandemic, seen from the government perspective of the government of Sorong City, in various efforts that were considered strategic, were taken into action and made into policies by the government in an effort to overcome the spread of the Covid-19 pandemic, including policy actions to overcome the impact it had on the social and cultural order of life. , and the economy of society that power relations. Distribution of drugs in government relations and drug trade in accordance with the applicable regulations implemented by PT. Rifanti Asti during the Covid-19 pandemic. The relationship between actors in the power network of parties positioned to be involved is a major concern in looking at situations related to health, which is always important on various occasions, regardless of various interests. Being wise in consuming information and knowledge is a strategy to accelerate the breaking of the chain of spread of the Covid-19 pandemic specifically in Sorong City and the entire West Papua Province.